A cross-sectional study to assess sub-clinical atherosclerosis in patients of psoriasis independent of metabolic syndrome - Shreya Deoghare; Hemant Talanikar; Mahendra S Deora; Rohit Kothari; Yugal K Sharma; Kalyan Dalve; Asmita Kapoor; Aishwarya Patil (Wolters Kluwer Medknow Publications, 2022)
Background: A sustained inflammatory state of psoriasis causes comorbidities such as psoriatic arthritis, metabolic syndrome (MetS), and cardiovascular disease. Aims: To note the duration and severity of psoriasis, assess prevalence of MetS, and correlate these with indicators of sub-clinical atherosclerosis. Methodology: Thirty-two patients of chronic plaque psoriasis were enrolled in the study. Their demographic particulars, clinical details, results of investigations to assess MetS, and indicators of sub-clinical atherosclerosis, namely, carotid intimal media thickness (CIMT) measured using B-mode USG and epicardial fat thickness (EFT) using 2-D ECHO, were recorded. Results: The study participants were predominantly male (2.5:1); their mean age was 40.45 ± 12.42 years, the median disease duration (DD) was 2 years, and the mean psoriatic area severity index (PASI) score was 8.62 ± 7.49. Mild disease (PASI <5) was present in 12 participants (37.5%), and shorter DD (<5 years) was present in 16 (50%) participants. MetS, detected in 11 (37.5%) study participants, was not significantly associated with CIMT, EFT, DD, and PASI. CIMT and EFT too did not correlate significantly with DD, PASI, or measures of MetS. Neither did there exist any significant correlation between CIMT and EFT. Conclusion: Sub-clinical atherosclerosis in our study participants was not significantly associated with either measures of MetS or duration/severity of psoriasis.